(3TaGA GdZdjd aj Md ebad Ndjds - (3eMeO Hf CMeO Hf eMeO Hf ZGRi GdecfGSis; (3Ndjd Hf ESMGb Hf ehSi, VjGA GdOjf GdoLrfpOj GdeGdcj GdeUQj,J (B776 (3g` s
(3ChdgG (B:s
(3jHOC GdLRA HHGH GdHjhY (B: (3bhdg (B: (3hefY ddJgeI eGcKQ , bUOI (B: (3cHjY hSda HefaYI s
(3BNQgG (B:s
(3BNQ GdehLhO efgG ef HGH GdhUjI (B:(3bhdg hcGaQ GHf YQaI (B: (3gh hGVM dCfgG YWjI ef eGdc JGe Gdedc s
(3GdLRA GdKGfi ef GdfSNI GdSGHbI faSgGs
(3fSNI eUMMIs
(3cJHJ YfGhjf GdCHhGH hGdaUhd hHYV GdcdeGJ HGdMeQIs
(3GdfSNI HgG MhGT s
(3HgG fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdeGdcjs